Involvement of the Wbp pathway in the biosynthesis of Porphyromonas gingivalis lipopolysaccharide with anionic polysaccharide - Shoji, Mikio (Nature Publishing Group, 2014)
The periodontal pathogen Porphyromonas gingivalis has two different lipopolysaccharide (LPS) molecules, O-LPS and A-LPS. We have recently shown that P. gingivalis strain HG66 lacks A-LPS. Here, we found that introduction of a wild-type wbpB gene into strain HG66 restored formation of A-LPS. Sequencing of the wbpB gene from strain HG66 revealed the presence of a nonsense mutation in the gene. The wbpB gene product is a member of the Wbp pathway, which plays a role in the synthesis of UDP-ManNAc(3NAc)A in Pseudomonas aeruginosa; UDP-ManNAc(3NAc)A is sequentially synthesized by the WbpA, WbpB, WbpE, WbpD and WbpI proteins. We then determined the effect of the PGN_0002 gene, a wbpD homolog, on the biosynthesis of A-LPS. A PGN_0002-deficient mutant demonstrated an A-LPS biosynthesis deficiency. Taken together with previous studies, the present results suggest that the final product synthesized by the Wbp pathway is one of the sugar substrates necessary for the biosynthesis of A-LPS.